(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Meningiomas of the perisellar region (the colliculus sellae, anterior clinoid process (ACP), lesser and medial parts of the greater wing of the sphenoid bone, and cavernous sinus) account for 20–25% of the total number of intracranial meningiomas [1, 4]. The leading symptom in the clinical course of perisellar meningiomas (PSM) is optic nerve (ON) dysfunction, caused not only by the volumetric effect of the tumor on the ON and chiasm, but also by tumor spread and nerve compression in the optic canal (OC). Cases of ON dysfunction caused by direct tumor spread into the optic canal (OC) deserve special attention. This limits the possibility of radical resection of these tumors and leads to unsatisfactory functional results in the postoperative period. Meningiomas tend to spread into the OC regardless of their size [7]. Leading neurosurgeons consider early extradural decompression of the ON (OD) and its maximum mobilization for tumor manipulation to be a key aspect of surgery for meningiomas extending into the OC. ON compression is eliminated not only by tumor removal in the OC, but also by partial resection of its bony walls without damaging the blood supply sources of the optochiasmal complex [2, 7]. This approach allows for more radical removal of the meningioma and preservation or improvement of ON function. It is not always possible to determine tumor extension into the OC at the surgical planning stage, even with the use of modern neuroimaging techniques (magnetic resonance imaging (MRI) and multislice computed tomography (MSCT)). The OD is an integral stage of surgical intervention, influencing both the radicality of the resection and its functional outcome. Various variants of bone decompression of the OC (BD) are used, in particular, the addition of OD with anterior clinoidectomy (ACE). The optic nerve endoscopy (ODS) is performed transcranially, intra- and extradurally. Surgical procedures involve removing the bony walls of the optic nerve, dissecting the falciform ligament, and, if necessary, the optic nerve sheath. An analysis of modern studies and publications devoted to the surgical treatment of meningiomas with extension into the optic nerve revealed different opinions regarding the appropriateness and method of optic nerve endoscopy. The rate of visual recovery in patients with meningiomas that extend into the optic nerve, depending on the tumor characteristics and initial visual acuity, ranges from 25 to 91% [4, 6].